A New Hypothesis on the Frequency Discrimination of the Cochlea - (:unkn) unknown (AVES, 2017)
OBJECTIVE: Medial olivocochlear efferent (MOCE) neurons innervate outer hair cells (OHCs) of the cochlea, which in turn leads to basilar membrane motion. We hypothesized that MOCE-induced alterations in basilar membrane motion, independent of traveling waves, is responsible for the cochlear frequency discrimination of sound. MATERIALS and METHODS: Eleven guinea pigs underwent bilateral otoscopic and audiologic evaluations under general anesthesia. The study comprised two parts. Part I (n=11) included spontaneous otoacoustic emission (SOAE) recordings with or without contralateral pure-tone acoustic stimuli (1 and 8 kHz) at 60 dB sound pressure level (SPL). Part II involved pure-tone (1 or 8 kHz) acoustic trauma in the right ears of two randomly selected subgroups (G1: 1 kHz; n=4 and G8: 8 kHz; n=4). The remaining three animals served as controls. After frequency-specific deafness was confirmed by distortion product otoacoustic emission (DPOAE), SOAEs were recorded in the left ears in the presence of a contralateral pure-tone (1 and 8 kHz) stimulus of 60 dB SPL. Furthermore, the surface of the organ of Corti was examined by scanning electron microscopy (SEM). RESULTS: The contralateral pure tone led to frequency-specific activation in SOAEs in part I (without trauma) and part II (with trauma) measurements. SEM showed heterogeneous OHC damage along the cochlea in traumatized ears with pure tone. CONCLUSION: We suggest that MOCEs convey acoustic information from traumatized ears to intact ears. Traumatized ears can show frequency-specific activation in the presence of diffuse damage in OHCs that excludes the passive transmission of the pressure wave from the perilymph to the basilar membrane.
Keywords: Efferent pathways; cochlear outer hair cells; otoacoustic emissions; spontaneous; basilar membrane; microscopy; electron; scanning; OUTER HAIR CELL; PRESTIN; AMPLIFICATION; FLOW